Does vibration benefit delayed-onset muscle soreness?: a meta-analysis and systematic review. Issue 1 (January 2019) - Lu, Xingang; Wang, Yiru; Lu, Jun; You, Yanli; Zhang, Lingling; Zhu, Danyang; Yao, Fei
Objective: Delayed-onset muscle soreness (DOMS) is a symptom of exercise-induced muscle injury that is commonly encountered in athletes and fitness enthusiasts. Vibration is being increasingly used to prevent or treat DOMS. We therefore carried out a meta-analysis to evaluate the effectiveness of vibration in patients with DOMS. Method: We searched nine databases for randomized controlled trials of vibration in DOMS, from the earliest date available to 30 May 2018. Visual analogue scale (VAS) and creatine kinase (CK) levels were set as outcome measures. Results: The review included 10 identified studies with 258 participants. The meta-analysis indicated that vibration significantly improved the VAS at 24, 48, and 72 hours after exercise, and significantly improved CK levels at 24 and 48 hours, but not at 72 hours. Conclusion: Vibration is a beneficial and useful form of physiotherapy for alleviating DOMS. However, further studies are needed to clarify the role and mechanism of vibration in DOMS.